The effects of 5% albumin and 4% gelatin solution on renal function, haemodynamic stability and blood loss in patient undergoing CABG (coronary artery bypass grafting in HUSM - Shahidan, Nur Zurairah (2017)
Background: The most ideal approach on cardiopulmonary bypass (CPB) priming and intravenous fluid choice during Coronary Artery Bypass Grafting (CABG) remains controversial. Methods: Thirty four patients undergoing elective CABG were studied. Patients were excluded if they scheduled for emergency CABG, on known nephrotoxic drug or have a history of allergy to colloid. Patients were randomly assigned to two groups of 5% albumin (n=18) and 4% gelatin (n=16). Haemodynamic parameters, serum level of urea, creatinine, sodium and urine level of sodium and creatinine was measured preoperatively, immediately after the operation, day 1, 2 and 3 post-operatively. Hemoglobin level was taken preoperatively, immediately post-operation, day 1 and 2 after operation. Cathecolamines and vasodilator requirement was also recorded until day 2 post operation. Glomerular filtration rate (GFR), Fractional Excretion of Sodium (FeNa) was calculated and compared. Results: mean difference of GFR was significantly higher in 4% gelatin group throughout the study but the FeNa difference was not statistically significant. On the topic of haemodynamic stability, the mean arterial blood pressure (MAP) during cardio pulmonary bypass was significantly higher in 5% albumin group (63.9±3.73 mmHg, P value=0.011). Cathecolamines and vasodilator requirement showed no remarkable difference. Intraoperative blood loss was lower in 5% albumin group with mean of 1425.33 (±451.81) mL whereas in 4% gelatin group 1514.44 (±697.67) mL but the difference was not significant(P value= 0.658). Intraoperatively, less blood transfusion was required in 5% albumin group(22.2%) compared to 4% gelatin group (43.8%)Conclusion: Administration of 5% albumin and 4% gelatin in patients undergoing CABG showed no remarkable difference on renal function parameters, haemodynamic stability and blood loss.